5
$\begingroup$

Evaluate :

$$\frac{dx}{x+ \sqrt{x^2-x+1}}$$

After dividing and multiply with $x-\sqrt{x^2-x+1}$, I get

$x+\ln |x-1|-\int \frac{\sqrt{x^2-x+1}}{x-1}dx$.

Is $\int \frac{\sqrt{x^2-x+1}}{x-1}dx$ is integrable in terms of elementary functions?

$\endgroup$
1
  • $\begingroup$ Have you learned hyperbolic substitution?? $\endgroup$ Jan 21 '17 at 3:48
4
$\begingroup$

We have $$I =\int \frac {\sqrt {x^2-x+1}}{x-1} dx =\frac {1}{2 }\int \frac {\sqrt {(2x-1)^2+3}}{x-1} dx $$ Substituting $u =2x-1$, we get, $$I =\frac {1}{2} \int \frac {\sqrt{u^2+3}}{u-1} du $$ Now perform hyperbolic substitution $u =\sqrt {3} \operatorname {sinh}(v)$ and simplifying gives us $$I =\frac {3}{2} \int \frac {(\operatorname {cosh }(v))^2}{\sqrt {3}\operatorname{sinh}(v) -1} dv $$ which can be solved by Weierstrass substitution. Hope it helps.

$\endgroup$
1
$\begingroup$

There is a substitution, called the Euler substitution, which solves your integral rather neatly. In your case we set $t = \sqrt{x^2 - x + 1} + x$; after subtracting $x$ from both sides and squaring, we get $x^2 -x + 1 = t^2 - 2xt + x^2$, which can be solved (after subtracting $x^2$ from both sides) to get $x = \frac{t^2 - 1}{2t - 1}$. In this case, $\frac{dt}{dx} = \frac{1}{\sqrt{x^2 - x + 1}}(2x-1) + 1$, and so

\begin{eqnarray} \int \frac{dx}{x + \sqrt{x^2 - x + 1}} = \int (\frac{1}{x + \sqrt{x^2 - x + 1}}\cdot\frac{1}{\frac{dt}{dx}})\frac{dt}{dx}dx \\= \int \frac{1}{t}\cdot\frac{1}{[\frac{1}{t - (t^2-1)/(2t-1)}\cdot(2(\frac{t^2-1}{2t-1}) - 1)] + 1} dt = \dots \\ \dots = \int\frac{t^2 - t + 1}{3t^3 - 3t^2} dt\end{eqnarray}

which is quite easy to solve directly by partial fractions.

$\endgroup$
1
  • $\begingroup$ $\frac{dt}{dx}=\frac1{\color{red}{2}\sqrt{x^2-x+1}}(2x-1)+1$ $\endgroup$
    – Invisible
    Oct 18 '20 at 17:16

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.